2015
DOI: 10.1007/s12540-015-4108-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of constraint condition on rolling behavior of magnesium alloy at low temperatures

Abstract: Influence of constraint condition on rolling behavior of a magnesium alloy sheet at low temperature was investigated by embedding the magnesium alloy sheet within a block of an aluminum alloy having a higher strength. Magnesium alloy sheets rolled with the aluminum alloy block exhibited better rolling capability at a low temperature of 373 K than the sheets rolled without the block. The constraint placed on the magnesium alloy sheet by the aluminum alloy block impedes the initiation of edge cracks in the sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…However, in the present study, as well in the literature [9,[29][30][31], the results show that, irrespective of the parameters such as pass reduction and rolling rate, there is edge cracking when the rolling has proceeded beyond a certain number of passes.…”
Section: Accepted M Manuscriptsupporting
confidence: 60%
“…However, in the present study, as well in the literature [9,[29][30][31], the results show that, irrespective of the parameters such as pass reduction and rolling rate, there is edge cracking when the rolling has proceeded beyond a certain number of passes.…”
Section: Accepted M Manuscriptsupporting
confidence: 60%
“…15 Wu T et al 12 selected Al alloy as a cover to pack ZE20, and the results showed that ZE20 sheets exhibited a fine recrystallized microstructure, good ductility, and weak texture. Kim et al 24 had proved that constraint placed on the Mg alloy by the aluminum (Al) alloy could impede the initiation of edge cracks in the sheet during rolling, and the main reason is that the aluminum reduces the tensile stress generated along the rolling direction near the edge region of the Mg alloy. Niu HZ et al 25 had used stainless-steel as a cover for Ti alloy during rolling and got full DRX microstructures.…”
Section: Introductionmentioning
confidence: 99%